2005
DOI: 10.1590/s1516-31802005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathy and acupuncture teaching at Faculdade de Medicina da Universidade de São Paulo: the undergraduates’ attitudes

Abstract: The medical students were interested in learning the principles of homeopathy and acupuncture, were able to observe and report on the effectiveness of these treatments and defended the use of these medical specializations within public healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
(31 reference statements)
1
15
0
13
Order By: Relevance
“…Com isto, também se esperava que a principal fonte de conhecimento dos estudantes fosse não acadêmica, como encontrado em seis dos estudos que também analisaram fontes de conhecimento 9,10,12,17,22,23 . Segundo Rampes et al 24 , a maioria das escolas médicas não provê educação formal sobre terapias complementares.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Com isto, também se esperava que a principal fonte de conhecimento dos estudantes fosse não acadêmica, como encontrado em seis dos estudos que também analisaram fontes de conhecimento 9,10,12,17,22,23 . Segundo Rampes et al 24 , a maioria das escolas médicas não provê educação formal sobre terapias complementares.…”
Section: Discussionunclassified
“…Entende-se que é dever do médico ter conhecimento míni-mo para discutir o uso de terapias complementares com seus pacientes 18,19,22,28,29 , e tal ato prepararia melhor os futuros médi-cos para solicitar informações, responder mais efetivamente às perguntas e estar aptos a avaliar a introdução ou remoção das terapias do plano terapêutico 23 .…”
Section: Discussionunclassified
“…Homeopathic medicine was introduced to Brazil in the XIX century and is currently ranked the 16th medical specialty with the largest contingent of professionals among 61 specialties analyzed in the survey conducted in 1996 7,8,23 . Nevertheless, only 17 schools of medicine among 115 analyzed in Brazil have been teaching homeopathic principles, and among these not all respect the minimum curriculum of 45 minutes per lesson as suggested by the Brazilian Homeopathic Medical Association 24 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Teixeira et al 7 , over 85% of the medical students at the University of São Paulo considered that homeopathy and acupuncture should be included in curricula, as options (72%) or compulsorily (19%); while 56% showed a great interest in learning about them. In another study conducted during a medical students' conference, Teixeira 8 found that 43% of students did not recognize homeopathy as a "medical specialty", they were all unaware that it was "available through public health services" 8 9 , only 40% (99) of 247 medical students, from the University of Campinas, correctly answered the questions about homeopathy principles and 25% of them were completely incorrect in their answers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, analysis and intervention concerning the historical, social and political determinants of the health-disease process are conducted 5,6 . One of these COMUNICAÇÃO SAÚDE EDUCAÇÃO 2014; 18(48):127- 38 resources targeted at integrality, and the main object of the present study, is the inclusion of complementary and alternative medical rationalities in medical education [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%